2015
DOI: 10.1016/j.polymertesting.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of torsional actuation in highly twisted yarns and fibres

Abstract: Highly twisted oriented polymer fibres and carbon nanotube yarns show large scale torsional actuation from volume expansion that can be induced, for example, thermally or by electrochemical charging. When formed into spring-like coils, the torsional actuation within the fibre or yarn generates powerful tensile actuation per muscle weight. For further development of these coil actuators and for the practical application of torsional actuators, it is important to standardise methods for characterising both the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 14 publications
3
50
0
Order By: Relevance
“…32 The twisting then coiling manipulation of precursor polymeric bers gives rise to muscles with outstanding performances, including energy densities as high as 2.63 kJ kg À1 , power densities over 5.3 kW kg À1 and strokes up to 49%. Most recently, a number of studies have been conducted on this class of muscles, including testing and characterization methods, [33][34][35] mathematical modeling, [22][23][24][25] and applications such as robotics, 31 morphing airplanes and vehicles, 28 and self-healing systems. 29,30 It is revealed that the negative coefficient of thermal expansion (NCTE) in the ber axial direction plays a critical role in muscle actuation.…”
mentioning
confidence: 99%
“…32 The twisting then coiling manipulation of precursor polymeric bers gives rise to muscles with outstanding performances, including energy densities as high as 2.63 kJ kg À1 , power densities over 5.3 kW kg À1 and strokes up to 49%. Most recently, a number of studies have been conducted on this class of muscles, including testing and characterization methods, [33][34][35] mathematical modeling, [22][23][24][25] and applications such as robotics, 31 morphing airplanes and vehicles, 28 and self-healing systems. 29,30 It is revealed that the negative coefficient of thermal expansion (NCTE) in the ber axial direction plays a critical role in muscle actuation.…”
mentioning
confidence: 99%
“…For example, heating monofilament nylon-6 fibers of different diameters from 26 o C -62 o C caused the fiber diameter to increase by ~2.5% [22] and a simultaneous reduction in modulus of ~10% [23]. As shown by equation (3), these two effects exactly cancel when coil geometries do not change so that the coil stiffness remains constant.…”
Section: Spring Stiffness Of Polymer Coil Musclesmentioning
confidence: 99%
“…Full recovery of the untwisting occurred when the volume expansion was reversed by discharging, but only when the yarn was connected to a non-actuating 'return spring' fiber. The effects of this and other testing configurations on the torsional actuation stroke and torque have been recently elaborated [23]. Forming composite yarns by impregnating the porous carbon nanotube or niobium nanowire twisted yarns with a guest material, such as paraffin wax, enabled the preparation of totally dry, electrolyte-free torsional muscles (Fig.…”
Section: Tensile -Torsional Actuation Coupling In Polymer Coil Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Training of the muscle is usually seen as repeating the actuation cycle in the setup a number of times before performing the actual experiment [5], [20], [21]. We let muscles undergo a number of cycles of heating and cooling, from room temperature to the maximum actuation temperature, in the intended setup.…”
Section: Trainingmentioning
confidence: 99%